Politics Under Electronic Simultaneity - V. P. Terin (Vestnik MGIMO-Universiteta)
In contradistinction to the book and the other typographic products, the electronic media operates on a 24-hour-a-day basis evoking simultaneity as the guiding mode of perception and thinking for all those under its influence. The discovery of this fact manifested itself in the formation and development of the managerial technologies operating by means of the electronic information environment and following the principle of simultaneity in the first place. Thus, at the end of the 1960s already the election campaigns in the U.S.A. began to operate on the basis of the final cause as the guiding principle of the country's mass consciousness motivating to carry out each particular event as if already rejoicing at the victory. With this in mind, there emerged a problem of applying this approach with its enormous managerial potential elsewhere. To add, simultaneity as a norm of perception and thinking turned out to be increasingly important with the advent of the electrical telegraph and the press relying on its short disconnected messages instantaneously arriving from all parts of the world. All the other media, which emerged in the wake of this development, has served to fortify this mode of thought as governing in the electronic information environment. The potential of the electronically operating global managerial technologies is quickly growing. The article also deals with the information overload and pattern recognition problem understood in managerial terms as well as mythologization and demythologization processes as they are necessitated by the electronic media coverage worldwide.